The Effect of Outline to Improve Students Writing' Ability at the Second Year Students of SMAN 3 Mamuju - Syahban Mada Ali; Nurul Hasanah (Edumaspul: Jurnal Pendidikan, 2020)
The Effects of Outline to Improve Students’ Writing Ability at the Second Year Students of SMAN 3 Mamuju. Outline is a useful tool to help writers get easier in developing their ideas. An outline can do two things: first, it can save a lot of rewriting and second, it allows writers to check quickly their paragraph’s unity. The aim of this research is to find out whether the use of outline can improve the students’ writing ability in a descriptive paragraph. The method used was true-experimental design. The subject of this research was class XI A students of SMAN 3 Mamuju. The data collected was from the test given to the students and was analyzed through quantitative method. To get the score, the researcher used scoring scale which includes the content, organization, vocabulary, language use and mechanics. The mean score, standard deviation, and t-test between the pre-test and post-test was calculated by using Jacob’s scoring rubric. The data analysis showed that the students’ got their mean score greater in the posttest than in the pretest, in which the mean score was 51.8 and 68.5. Moreover, the t-test value (25.064) was also higher than the t-table value (2.045), which is meant the treatment of outline strategy gave a significant improvement to the students’ writing ability of SMAN 3 Mamuju.